Repair for Congenital Macrostomia: Vermilion Square Flap Method - Renuka Dhingra; Asheesh Dhingra; Dipti Munjal (Case Reports in Dentistry)
Transverse facial clefts (macrostomia) are rare disorders that result when the embryonic mandibular and maxillary processes of the first branchial arch fail to fuse due to failure of mesodermal migration and merging to obliterate the embryonic grooves between the maxillary and mandibular processes to form the angle of the mouth at its normal anatomic position. Macrostomia may be seen alone or in association with other anomalies. It may be unilateral, extending along a line from the commissure to the tragus or bilateral. It is usually partial but rarely complete. Transverse facial clefts are more common in males and more common on the left side when unilateral. The goal of macrostomia reconstruction is to achieve functional, symmetrical, and accurate oral commissure with minimal scar. In this paper, we present a six-year-old girl with unilateral macrostomia with preauricular skin tags and malformation of pinna on ipsilateral side treated with vermillion-square flap method. The scar is placed at the upper lip. At two-month followup, the oral commissures are symmetric, the scars are inconspicuous, and the overall balance of facial contour and lip is excellent. We recommend this method for patients with mild to moderate macrostomia.